Sub-Saharan Africa Refinery Project, Volume II-A : Refinery Study - World Bank (Washington, DC, 2013)
The Sub-Saharan Africa Refinery Study evaluates the effects of improved fuel specifications on refiningoperations and air quality in Sub-Saharan Africa (SSA). The improved fuel specifications would reduce the levels of certain pollutants in fuels, in turn reducing human exposure to these pollutants in ambient air. The health study estimates the health impacts and associated monetary benefits associated with the proposed improvements in fuel quality. The estimated monetary benefits will be compared to the costs to the refining industry associated with a change in fuel specifications, by region, as presented in Volume II,the Refinery Study